Base-delta-immediate compression: Practical data compression for on-chip caches - Pekhimenko, Gennady; Seshadri, Vivek; Mutlu, Onur; Kozuch, Michael A.; Gibbons, Phillip B.; Mowry, Todd C. (PACT'12 : proceedings of the 21st International Conference on Parallel Architectures and Compilation Techniques, September 19-23, Minneapolis, Minnesota, USA, 2012)
Cache compression is a promising technique to increase on-chip cache capacity and to decrease on-chip and off-chip bandwidth usage. Unfortunately, directly applying well-known compression algorithms (usually implemented in software) leads to high hardware complexity and unacceptable decompression/compression latencies, which in turn can negatively affect performance. Hence, there is a need for a simple yet efficient compression technique that can effectively compress common in-cache data patterns, and has minimal effect on cache access latency.